2012
DOI: 10.1007/s10103-012-1060-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of He-Ne and Ga-Al-As laser light on the healing of hard palate mucosa of mice

Abstract: Low-level laser therapy (LLLT) has been used to accelerate wound healing, yet questions remain concerning its therapeutic applications. This study aimed to compare the healing efficacy of helium-neon (He-Ne) red light (laser) and gallium aluminum arsenide (Ga-Al-As) infrared lasers at two different doses on hard palate wounds. In a randomized controlled study, 75 adult male mice were divided into five groups of 15 each, after undergoing identical surgical procedures; a control group, with no laser irradiation;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…This result can probably be explained by the effects of the GaAIAs laser wavelength and the applied dose on the secretory activity of fibroblasts, as well as their influence on the pro-and anti-inflammatory cytokines during early stages of repair, as previously reported [12,14,22]. A study conducted by Mendez et al [23] compared the influence of 20 and 50 J/ cm 2 doses on skin wound closure in rats; after 3 days repair, the group treated with 50 J/cm 2 had histologically significant regressions of inflammation and the presence of organized collagen matrix, with reduced collagen deposition noted after 5 days of healing.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This result can probably be explained by the effects of the GaAIAs laser wavelength and the applied dose on the secretory activity of fibroblasts, as well as their influence on the pro-and anti-inflammatory cytokines during early stages of repair, as previously reported [12,14,22]. A study conducted by Mendez et al [23] compared the influence of 20 and 50 J/ cm 2 doses on skin wound closure in rats; after 3 days repair, the group treated with 50 J/cm 2 had histologically significant regressions of inflammation and the presence of organized collagen matrix, with reduced collagen deposition noted after 5 days of healing.…”
Section: Discussionmentioning
confidence: 63%
“…Diverse studies have used wavelengths between 680 and 840 nm, which are related to the most efficient tissue biostimulation [12]. Evidence regarding the healing efficacy of low-level laser therapy techniques using gallium aluminum arsenide (Ga-Al-As) infrared lasers at different doses on hard palate wounds in mice showed that laser application has a positive healing effect on the healing process [14].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we demonstrated that both, red (635 nm) and NIR (810 nm) light can significantly enhance the healing of partial-thickness dermal abrasions. Similarly, other studies have also reported that He-Ne laser (632.8 nm) and other wavelengths (660–670 nm) irradiation at fluence of 1–6 J/cm 2 stimulated healing in normal and impaired wounds (burns and diabetic) by re-epithelialization and granulation tissue formation [8, 9, 11, 27, 28]. …”
Section: Discussionmentioning
confidence: 66%
“…Fahimipour et al. suggested that LLLT inhibits severe inflammatory reactions and promotes collagen formation with diode laser wavelengths of 685 and 830 nm at doses of 3.95 and 7.9 J/cm2.…”
Section: Discussionmentioning
confidence: 99%
“…. The density of collagen fibers was scored according to the following scale: 1 = few collagen fibers, 2 = few and partially spread collagen fibers, 3 = few and fully spread collagen fibers, and 4 = dense collagen fibers (Tables and ). To avoid observer bias, the histologist was blinded to the study groups, and the data were recorded with respect to the sample codes.…”
Section: Methodsmentioning
confidence: 99%